Needle EMG of Thenar Muscles in Less Severe Carpal Tunnel Syndrome. Issue 6 (November 2018) - Rubin, Devon I.; Dimberg, Elliot L.
Abstract : Introduction: The value of needle electromyography (EMG) in thenar muscles in patients with less severe carpal tunnel syndrome is controversial. Methods: Patients referred for electrodiagnostic testing for carpal tunnel syndrome, in which nerve conduction study demonstrated median sensory nerve conduction study abnormalities and either normal median motor nerve conduction study or only prolonged median motor distal latencies (DLs) (with normal amplitudes) were prospectively studied. Patients with low-median compound muscle action potential amplitudes or any other EMG abnormality were excluded. Needle EMG of a thenar muscle was performed to assess for the presence and grade of fibrillation potentials and motor unit potential abnormalities. The frequency of abnormalities was recorded. Statistical comparison between patients with and without needle EMG abnormalities was performed. Results: One-hundred two patients were included (50 with normal median motor DLs and 52 with abnormal DLs). Minimal or equivocal thenar needle EMG abnormalities were found in 12% of subjects with normal DLs. In patients with abnormal DLs, 32.6% had abnormalities, 15.4% with a mild degree of fibrillation potentials, and 25.0% with mild motor unit potential abnormalities. Patients with abnormal DLs and needle EMG abnormalities had significantly lower compound muscle action potential amplitudes compared to those without needle EMG changes. Conclusions: Patients with carpal tunnel syndrome with no involvement of the median motor nerve conduction study are unlikely to demonstrate prominent abnormalities on needle EMG of thenar muscles, and needle EMG of the thenar muscles is not necessary. However, in patients with carpal tunnel syndrome in which the median motor DL is prolonged but compound muscle action potential amplitudes are absolutely normal, needle EMG should be considered, as it may provide value in indicating some axonal loss despite a normal median compound muscle action potential amplitude.